Analisis Efektivitas Media Sosial sebagai Instrumen Edukasi Pajak terhadap Generasi Milenial dan Gen Z - Delvina Septia Pritama; Desy Ismah Anggraini (PENG: Jurnal Ekonomi dan Manajemen, 2026)
This study aims to analyze the effectiveness of social media as an instrument for tax education among Millennials and Generation Z in Indonesia. The background of this research lies in the low level of tax literacy and compliance among young people, despite being the most active social media users and a dominant segment of the productive age population. Using a quantitative descriptive and explanatory approach, data were collected from 200 respondents aged 17–35 through an online survey. The results show that social media—especially TikTok and Instagram—is effective in improving understanding and shaping positive attitudes toward tax obligations. Regression analysis reveals that the intensity of exposure to tax-related content has a significant influence on tax knowledge, with an R² value of 41.1%. Most respondents reported that visual, concise, and interactive content is easier to understand and encourages actions such as registering for a Taxpayer Identification Number (NPWP) or using the e-Filing system. This study recommends that the Directorate General of Taxes and related institutions strengthen their digital communication strategies through collaborative, creative, and credible approaches to foster tax awareness among younger generations.